2019
DOI: 10.1093/cercor/bhz310
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Dmrt5 Affects the Formation of the Subplate and Early Corticogenesis

Abstract: Dmrt5 (Dmrta2) and Dmrt3 are key regulators of cortical patterning and progenitor proliferation and differentiation. In this study, we show an altered apical to intermediate progenitor transition, with a delay in SP neurogenesis and premature birth of Ctip2+ cortical neurons in Dmrt5−/− mice. In addition to the cortical progenitors, DMRT5 protein appears present in postmitotic subplate (SP) and marginal zone neurons together with some migrating cortical neurons. We observed the altered split of preplate and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 99 publications
2
16
0
Order By: Relevance
“…Despite the central position of subplate neurons in orchestrating cortical connectivities, the molecular determinants of subplate wiring function remain largely elusive. Previous studies have focused on genes selectively expressed in subplate neurons Oeschger et al, 2012), which are found to mediate subplate neuron specification, migration, and axon development (Arai et al, 2019;Caviness, 1982;Han et al, 2011;Hevner et al, 2001;Kwan et al, 2008;Lai et al, 2008;Rakic et al, 2006;Ratie et al, 2019;Tiong et al, 2019). Here, by cell type-specific dissection of cortical Arid1a function, we uncover a surprisingly selective role for a ubiquitously-expressed chromatin remodeler in establishing the molecular identity and mediating the non-cell autonomous circuit wiring function of subplate neurons.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Despite the central position of subplate neurons in orchestrating cortical connectivities, the molecular determinants of subplate wiring function remain largely elusive. Previous studies have focused on genes selectively expressed in subplate neurons Oeschger et al, 2012), which are found to mediate subplate neuron specification, migration, and axon development (Arai et al, 2019;Caviness, 1982;Han et al, 2011;Hevner et al, 2001;Kwan et al, 2008;Lai et al, 2008;Rakic et al, 2006;Ratie et al, 2019;Tiong et al, 2019). Here, by cell type-specific dissection of cortical Arid1a function, we uncover a surprisingly selective role for a ubiquitously-expressed chromatin remodeler in establishing the molecular identity and mediating the non-cell autonomous circuit wiring function of subplate neurons.…”
Section: Introductionmentioning
confidence: 82%
“…Molecular studies have largely focused on subplate-enriched genes Oeschger et al, 2012). Together, these studies have characterized molecular determinants of subplate neuron specification, migration, and axon development (Arai et al, 2019;Caviness, 1982;Han et al, 2011;Hevner et al, 2001;Kwan et al, 2008;Lai et al, 2008;Rakic et al, 2006;Ratie et al, 2019;Tiong et al, 2019), highlighting the complex genetic regulation required for subplate neuron development. The severe axon misrouting phenotypes of subplate ablation (Ghosh et al, 1990;Shatz, 1992, 1993), however, are not broadly recapitulated in these genetic mutants, precluding further mechanistic investigations into the circuit wiring functions of subplate neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the central position of SPNs in orchestrating cortical connectivities, the molecular determinants of SP wiring functions remain largely elusive. Previous studies have focused on genes selectively expressed in SPNs (23,31) and illuminated the genetic bases of SPN specification, migration, and axon development (32)(33)(34)(35)(36)(37)(38). The axon misrouting phenotypes of SP ablation (17)(18)(19), however, are not broadly recapitulated in these genetic mutants.…”
mentioning
confidence: 99%